2021
DOI: 10.1007/s12046-021-01704-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the unsteady flow field in the human pulmonary acinus

Abstract: Understanding of airflow dynamics in the human pulmonary acinus is important for increasing targeted drug effectiveness and determining the health impact of toxic aerosols. However, there is a lack of quantitative data about the pulmonary airflow in realistic and flexible idealized geometries. This paper aims to numerically analyse the flow field of the pulmonary acinus using the computational fluid dynamics (CFD) model during transient breathing. Three-dimensional models with rhythmically expanding-contractin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The UFA field in the humanoid pulmonic was once again numerically reproduced by Ciloglu 35 . In a rotating annulus area with a control law kernel, Javaid et al 36 reported UFA of fractional Burgers' fluid. UFA in a side station pump with a curved blade was described by Zhang et al 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The UFA field in the humanoid pulmonic was once again numerically reproduced by Ciloglu 35 . In a rotating annulus area with a control law kernel, Javaid et al 36 reported UFA of fractional Burgers' fluid. UFA in a side station pump with a curved blade was described by Zhang et al 37 .…”
Section: Introductionmentioning
confidence: 99%